Genetic Susceptibility to Postdiarrheal Hemolytic-Uremic Syndrome After Shiga Toxin–Producing Escherichia coli Infection: A Centers for Disease Control and Prevention FoodNet Study. (6th December 2017) - Kallianpur, Asha R; Bradford, Yuki; Mody, Rajal K; Garman, Katie N; Comstock, Nicole; Lathrop, Sarah L; Lyons, Carol; Saupe, Amy; Wymore, Katie; Canter, Jeffrey A; Olson, Lana M; Palmer, Amanda; et al.
Abstract : This genetic study of carefully ascertained foodborne illness was conducted among patients hospitalized with acute Shiga toxin–producing Escherichia coli –related diarrhea. Novel variants associated with postdiarrheal hemolytic-uremic syndrome were identified in endothelial function, platelet function, iron transport, and innate immune response genes. Abstract: Background: Postdiarrheal hemolytic-uremic syndrome (D+HUS) following Shiga toxin–producing Escherichia coli (STEC) infection is a serious condition lacking specific treatment. Host immune dysregulation and genetic susceptibility to complement hyperactivation are implicated in non–STEC-related HUS. However, genetic susceptibility to D+HUS remains largely uncharacterized. Methods: Patients with culture-confirmed STEC diarrhea, identified through the Centers for Disease Control and Prevention FoodNet surveillance system (2007–2012), were serotyped and classified by laboratory and/or clinical criteria as having suspected, probable, or confirmed D+HUS or as controls and underwent genotyping at 200 loci linked to nondiarrheal HUS or similar pathologies. Genetic associations with D+HUS were explored by multivariable regression, with adjustment for known risk factors. Results: Of 641 enrollees with STEC O157:H7, 80 had suspected D+HUS (41 with probable and 32 with confirmed D+HUS). Twelve genes related to cytokine signaling, complement pathways, platelet function, pathogen recognition, iron transport, and endothelial function were associated with D+HUS in multivariable-adjusted analyses ( P ≤ .05). Of 12 significant single-nucleotide polymorphisms (SNPs), 5 were associated with all levels of D+HUS (intergenic SNP rs10874639, TFRC rs3804141, EDN1 rs5370, GP1BA rs121908064, and B2M rs16966334), and 7 SNPs (6 non–complement related) were associated with confirmed D+HUS (all P < .05). Conclusions: Polymorphisms in many non–complement-related genes may contribute to D+HUS susceptibility. These results require replication, but they suggest novel therapeutic targets in patients with D+HUS.